Komodifikasi Berita Iklan Natif Tumpahan Minyak Pertamina pada Program Berita Metro TV - Muchamad Fauzi Djamal (LPPM Universitas Sangga Buana, 2026)
Native advertising has been used in television programs that are inserted in news programs that discuss real problems. Native advertising does not highlight the promotional or commercial aspects by adopting the form and function of the news. This study aims to analyze the mechanism of using native advertising in the news of the Pertamina crude oil spill on Metro TV. Using the framework of Vincent Mosco's Media Political Economy Theory, this study dissects how news content is transformed into an economic commodity that serves the interests of advertisers. The research was conducted through a qualitative approach with a case study method, using in-depth interview techniques, analysis, and observation of news broadcasts. The results of the study show that Pertamina's oil spill news has undergone an intensive process of content commodification through a built-in content format and formed political economic relations that are able to intervene in the newsroom. This relationship resulted in a softening of journalistic narratives that prioritized the company's positive image. This process proves that the political economy mechanism through native advertising has converted the function of social media control into an instrument of corporate image recovery.